Investigation of Static Flexural Strength of Aluminium Honeycomb Panels with Varying Cell Sizes - Yusuf Siahaan, Muhammad Yusuf Rahmansyah Siahaan; Siregar, Rakhmad Arief (DINAMIS, 2024)
In this paper, the static flexural strength of aluminium honeycombs with varying cell sizes were tested experimentally using three-point bending method. Three different cell sizes, namely 2 mm, 4 mm and 6 mm, which were produced in a local workshop in the city of Medan, were used for this study. The main focus is to observe the maximum load and permanent deflection under static loads. The results show that the fracture mode that occurs after reaching the maximum load is core fracture followed by rupture of the adhesive between the core and the skin sheet. It is found that cell size has a significant influence on the maximum flexural strength of honeycomb panels which can be approximated by a regression curve with the results a1 = 0.3475 and a0 = 1.51.